2020
DOI: 10.1111/jcmm.16171
|View full text |Cite
|
Sign up to set email alerts
|

Carbofuran accelerates the cellular senescence and declines the life span of spns1 mutant zebrafish

Abstract: Senescence is a cellular process that implements permanent cell cycle arrest in response to various stimuli, such as oxidative stress, telomere loss, chemotherapeutic drugs, DNA damage and oncogenic signalling. 1,2 The elevated intensity of senescent cells mainly exists in ageing tissues, because of its implication with ageing. 1 Ablation of senescent cells by mechanical or other means improve health outcome as well as prolongs biological ageing. 3 Activation of senescence-associated beta-galactosidase (SA-β-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…As has been previously shown, spns1 −/− mutant larvae show increased lysosomes by 3.5 dpf ( Figure 1 A,B) [ 12 , 25 , 26 ]. Although beta-galactosidase [ 16 ] has been observed in spns1 −/− muscle, the effects of lacking spns1 on muscle structure have not previously been reported.…”
Section: Resultssupporting
confidence: 74%
“…As has been previously shown, spns1 −/− mutant larvae show increased lysosomes by 3.5 dpf ( Figure 1 A,B) [ 12 , 25 , 26 ]. Although beta-galactosidase [ 16 ] has been observed in spns1 −/− muscle, the effects of lacking spns1 on muscle structure have not previously been reported.…”
Section: Resultssupporting
confidence: 74%
“…2,15 Recently, we reported that carbofuran hastens the developmental senescence in spns1-mutant zebrafish and affects their lifespan. 16 The current study extends the report in wild zebrafish, whereas we found carbofuran affects cellular autophagy and accelerates developmental senescence in both wild and spns1-mutant zebrafish.…”
Section: D B a E Fsupporting
confidence: 88%
“…In survival analysis, we reconfirmed that carbofuran exposure significantly shortened the lifespan of spns1 ‐mutant zebrafish (Figure 1E ). 16 Additionally, using a real‐time survival study, we found carbofuran significantly abated the survival lengths of wild zebrafish (Figure 1F ), suggesting carbofuran affects lifespan of both wild and spns1 −/− mutant fishes.…”
Section: Resultsmentioning
confidence: 85%
“…Higher carbofuran doses can also disrupt the metabolism of cells, including Purkinje cells. This disruption can interfere with the normal function of these cells and lead to cell death [17]. High carbofuran doses can damage cellular structures, including cell membranes and organelles.…”
Section: Resultsmentioning
confidence: 99%